PENGARUH KOMPETENSI, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING DI KANTOR WILAYAH DIREKTORAT JENDERAL KEKAYAAN NEGARA JATENG DAN DAERAH ISTIMEWA YOGYAKARTA - Rahayu Triastity, Martono, Amin Wahyudi & (Universitas Slamet Riyadi, 2018)
The purpose of this study are (1) Analyzing the significance of theinfluence of competence, motivation, organizational culture, andorganizational commitment to performance. (2) Analyzing the significance ofcompetence, motivational, and organizational culture influences moderatedby organizational commitment to performance variable. The purpose of thisstudy were (1) This type of research is quantitative research. This researchtakes place in the Regional Office of the Directorate General of State Assets(DJKN) Central Java and the Special Region of Yogyakarta. The populationof 300 employees is divided into 7 regions. Samples taken as many as 100employees divided into 7 areas, sampling with propotionate cluster randomsampling. Data completion technique with questionnaire Data analysistechnique with multiple linear regression analysis and MRAanalysis.Research result. (1) competence variables significantly influenceemployee performance. (2) variable of motivation have an effect on signifikanto employee performance. (3) organizational culture variables have asignificant effect on employee performance. (4) organizational commitmentvariable has a significant effect on employee performance. (5) The moderatevariable1 (the interaction between competence and organizationalcommitment) is not significant. (6) The moderate variable1 (the interactionbetween motivation and organizational commitment) is not significant. (7)The moderate variable1 (the interaction between organizational culture andorganizational commitment) is not significant.Keywords: competence, motivation, organizational culture, organizationalcommitment, employee performanceÂ